Analisis permasalahan praktikum pada pembelajaran IPA kelas V di MI - Faizah, Laellis Nur; Marmoah, Sri; Hadiyah, Hadiyah (Didaktika Dwija Indria, 2021)
This study aims to determine the problem of science learning practicum at MI Baitul Huda Sumur. Thes subjects of this study were the 5th grade students of MI Baitul Huda Sumur. This reseach is a qualitative descriptive study with a case study research type. The data collection techniques in this study were questionnaires, interviews, and observations. Practical problem data obtained from teachers and students. Researchers made direct observations in the field to see the facilities and infrastructure for practicum in schools. By using five problem indicators, namely facilities dan infrastructure, knowledge, strategy, assesments, and constraint. Using triangulation sources and triangulation techniques. Obtained the result that the use of facilities and infrastructure in schools is still low.